Increase in Volumetric Electrical Power Density of a Linear Generator by Winding Optimization for Wave Energy Extraction - Selim Molla; Omar Farrok; Abidur Rahman; Md. Samiul Bashir; Md. Rabiul Islam; Abbas Z. Kouzani; M. A. Parvez Mahmud (IEEE Access)
In this article, a method of winding optimization of the linear generator is proposed to increase the electrical power generation from the oceanic wave. A linear generator is designed in the ANSYS/Maxwell environment to analyze the proposed winding optimization method. The electrical and magnetic properties of the generator are extensively analyzed. The cross-sectional area and the number of turns of the copper conductor are optimized to maximize the output power. Load characteristics are also considered for different conductor sizes and turn numbers to determine a suitable operating point. A cooling system is also incorporated in the optimized linear generator to extract the thermal energy produced during the operation, which eventually enhances the electrical power generation. It is found that the optimized linear generator finally generates around 42% more electrical power compared to that of the conventional one. Therefore, the volumetric power density of the linear generator is noticeably increased with the proposed optimization method that also results in the minimization of material cost of the generator. A downscale prototype of the linear generator is constructed in the laboratory. It is expected that the proposed winding optimization method can be used in designing other linear generators.